2019
DOI: 10.1523/eneuro.0354-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of NMDA Receptors at Ventral Hippocampal Synapses in the Infralimbic Cortex Regulates Cued Fear

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…However, they do not necessarily influence memory intensity upon retrieval and expression. Instead, they could allow adjustments in mechanisms supporting the original aversive memory to retain the extinction one 21,[42][43][44] . For instance, whereas fear conditioning was sufficient to depress the IL intrinsic excitability 18,19 , fear extinction produced the opposite outcome 45 .…”
Section: Discussionmentioning
confidence: 99%
“…However, they do not necessarily influence memory intensity upon retrieval and expression. Instead, they could allow adjustments in mechanisms supporting the original aversive memory to retain the extinction one 21,[42][43][44] . For instance, whereas fear conditioning was sufficient to depress the IL intrinsic excitability 18,19 , fear extinction produced the opposite outcome 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The glutamatergic projections from vCA1 to basolateral amygdala (BLA) encode conditioned fear memory whereas glutamatergic projections to the central amygdala (CeA) are necessary for the reinstatement of a cued fear response (e.g., freezing) following extinction (Xu et al, 2016 ; Jimenez et al, 2018 ). On the other hand, the regulation of conditioned fear extinction and renewal by vHPC seems to be via its glutamatergic projections to the infralimbic (IfL) and prelimbic (PrL) prefrontal cortices, respectively (Sierra-Mercado et al, 2011 ; Soler-Cedeño et al, 2019 ; Vasquez et al, 2019 ). Furthermore, there is a population of neurons within vCA1 that project monosynaptically to both the medial PFC and BLA that have been found to be preferentially activated during fear renewal (Jin and Maren, 2015 ) and are suspected to be important in conditioned fear extinction (Ishikawa and Nakamura, 2006 ; Kim and Cho, 2017 ).…”
Section: Vhpc As An Arbitrator Of Conflicting Stimulimentioning
confidence: 99%
“…shown that the subregions of the mPFC (such as the PrL, IL, and Cg1) play separate roles in fear conditioning and PTSD symptoms [33]. Previous studies have reported some controversial evidence in this regard [20,[34][35][36][37]. For example, a study of fear conditioning discrimination showed that Behavioural Neurology the subdivisions of the mPFC activated different responses to fear discrimination learning, and the PrL and IL seemingly contributed counterbalanced roles in fear discrimination learning [34].…”
Section: The Mpfc and Ptsd A Growing Body Of Evidence Hasmentioning
confidence: 99%
“…Using the single prolonged-stress footshock procedure of the PTSD model indicated that the prefrontal cortex has lower BDNF levels [19]. BDNF secretions in the ventral hippocampus-infralimbic cortex (IL) pathway could alter the fear contextual conditioning [20]. Under long-term restraint stress, the basolateral amygdala (BLA) exhibited higher levels in BDNF protein and BDNF mRNA expression; moreover, the CA3 of the hippocampus has lower BDNF protein and BDNF mRNA expression [21].…”
Section: Introductionmentioning
confidence: 99%